Проза 1912 - 1915 гг. - Кузмин М. А. (1999)
На тит. л. загл. не указано; Загл. указано на обороте тит. л. Экземпляры: ф-8 (ретроконверсия) / Инвентарный номер: 38301 / Цена: 95.00 / Сис.шифр: Р2 / Авт.знак: К 89 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6